Software Architecture Superstream Series Software Architecture Fundamentals - Ford, Neal; Newman, Sam; Richards, Mark; Schutta, Nathaniel; Parsons, Rebecca (O'Reilly Media, Inc., 2020)
This three-part series of half-day online events, hosted by chair Neal Ford, focuses on the hottest topics in software architecture-including microservices, essential architecture principles, and event-driven architecture and domain-driven design-giving you the insights to keep pace with what's next while still accommodating legacy needs. Both seasoned software architects and those looking to break into the field will learn new skills and the latest information on the tools and technologies they need to succeed. In Part 1, Software Architecture Fundamentals, the sessions give you a solid grasp of the fundamentals, preparing you to implement the strategies that will help your organization increase performance, reduce costs, manage complexity, build in resilience and scalability, and speed time to market. The four sessions from Rebecca Parsons, Nathaniel Schutta, Mark Richards and Sam Newman provide insight, advice, and essential knowledge you need to transition from developer to architect. About the presenters: Neal Ford is a director, software architect, and meme wrangler at ThoughtWorks, a software company and a community of passionate, purpose-led individuals who think disruptively to deliver technology to address the toughest challenges, all while seeking to revolutionize the IT industry and create positive social change. He's an internationally recognized expert on software development and delivery, especially in the intersection of Agile engineering techniques and software architecture. Neal has authored seven books (and counting), a number of magazine articles, and dozens of video presentations and spoken at hundreds of developers conferences worldwide. His topics include software architecture, continuous delivery, functional programming, cutting-edge software innovations, and a business-focused book and video on improving technical presentations. Check out his website, Nealford.com. Rebecca Parsons is CTO at ThoughtWorks. Rebecca has more than 30 years' experience leading the creation of large-scale distributed, services-based applications and the integration of disparate systems. Previously, she was an assistant professor of computer science at the University of Central Florida and a director's postdoctoral fellow at the Los Alamos National Laboratory. Rebecca's interests include parallel and distributed computation, programming languages, domain-specific languages, evolutionary architecture, genetic algorithms, and computational scien...
Online resource; Title from title screen (viewed June 18, 2020)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos